Corrigendum: How green is our valley?: five-year study of selected LIS journals from Taylor & Francis for green deposit of articles. (12th September 2018) - Emery, Jill
Following the publication of our recent article in Insights [https://insights.uksg.org/articles/10.1629/uksg.406/ ] we wish to bring the following corrigendum to your attention.